Disparities in Characteristics, Access to Care, and Oncologic Outcomes in Young-Onset Colorectal Cancer at a Safety-Net Hospital. Issue 5 (May 2021) - Fangman, Benjamin D.; Goksu, Suleyman Y.; Chowattukunnel, Nivan; Beg, Muhammad S.; Sanford, Nina N.; Sanjeevaiah, Aravind; Cox, John; Folkert, Michael R.; Aguilera, Todd A.; Mathews, Joselin; Pogacnik, Javier Salgado; Khatri, Gaurav; et al.
Abstract : PURPOSE: Young-onset colorectal cancer is an emerging cause of significant morbidity and mortality globally. Despite this, limited data exist regarding clinical characteristics and outcomes, particularly in safety-net populations where access to care is limited. We aimed to study disparities in clinical characteristics and outcomes in patients with young-onset colorectal cancer in the safety-net setting. METHODS: We performed a retrospective review of patients < 50 years old diagnosed and/or treated for colorectal cancer between 2001 and 2017 at a safety-net hospital. Kaplan-Meier and Cox regression models were constructed to compare overall survival (OS), progression-free survival (PFS), and relapse-free survival (RFS) by race and ethnicity, stratifying for relevant clinical and pathologic factors. RESULTS: A total of 395 young-onset patients diagnosed at a safety-net hospital were identified and 270 were included in the analysis (49.6% Hispanic, 25.9% non-Hispanic Black, 20.0% non-Hispanic White, and 4.4% other). Non-Hispanic White race was independently associated with worse OS (hazzard ratio [HR], 0.53; 95% CI, 0.29 to 0.97), as were lack of insurance, higher clinical stage, and mismatch repair proficiency. There was no significant difference seen in PFS or RFS between racial and ethnic groups. CONCLUSION: Non-Hispanic White race or ethnicity was found to be independently associated with worse OS in a safety-net population of patients with young-onset colorectal cancer. Other independent predictors of worse OS include higher stage, lack of insurance, and mismatch repair proficiency.